Komplikasi intratemporal dan intrakranial pada otitis media akut anak - Harim Priyono; Ratna Dwi Restuti; Andre Iswara; Setyo Handryastuti (Oto Rhino Laryngologica Indonesiana, 2011)
Background: Acute otitis media (AOM) is an acute inflammation in the middle ear caused by various factors such as blockage of Eustachian tube, infection and allergy. Purpose: The case report is to forewarn general practitioners and ENT specialists concerning AOM potentially causes intratemporal and intracranial complications. Case: We report an eleven-years-old girl with acute otitis media with intratemporal complications (labirynthitis and sensorineural hearingloss) and intracranial complication (meningitis). Case management: The recent management of acute otitis media with complications includes  empiric antibiotics, analgesic, anti-inflammatory drugs and miringotomy with ventilation tube insertion. Conclusion: The accuracy of diagnosing AOM with complication depends on the clinical symptomps such as vertigo, fever, seizure, meningism and unconsciousness. The pneumatic otoscopy examination is the gold standard in diagnosing AOM. Our patient was given antibiotics for 14 days, anti- inflamation and myringotomy with ventilation tube insertion procedure. Keywords: acute otitis media, intracranial complications, intratemporal complications    Abstrak :  Latar belakang: Otitis media akut (OMA) merupakan peradangan akut yang berlangsung di telinga tengah akibat berbagai faktor predisposisi seperti sumbatan tuba Eustachius, infeksi dan alergi.Tujuan: Kasus ini diajukan untuk mengingatkan dokter umum maupun spesialis THT mengenali gejala komplikasi OMA pada anak yang mempunyai potensi menimbulkan komplikasi intratemporal dan intrakranial. Kasus: Dilaporkan satu kasus OMA dengan komplikasi intratemporal (labirintitis dan tuli saraf) dan intrakranial (meningitis) pada anak perempuan usia 11 tahun.Penatalaksanaan: Penatalaksanaan otitis media akut dengan komplikasi intrakranial dan intratemporal mencakup pemberian antibiotik empiris, analgetik, anti-inflamasi dan tindakan miringotomi dengan pemasangan pipa ventilasi. Kesimpulan: Ketepatan dalam mendiagnosis OMA dengan komplikasi tergantung pada gejala klinis yang bisa dikenali seperti pusing berputar, demam, kejang, kaku kuduk dan penurunan kesadaran. Pemeriksaan otoskopi pneumatik merupakan gold standard dalam membantu diagnosis. Terapi untuk kasus ini terdiri atas antibiotik selama 14 hari, anti-inflamasi dan tindakan berupa miringotomi dengan pemasangan pipa ventilasi.Kata kunci: otitis media akut, komplikasi intrakranial, komplikasi temporal